2006
DOI: 10.1002/cncr.22054
|View full text |Cite
|
Sign up to set email alerts
|

Current controversies in high‐dose‐rate versus low‐dose‐rate brachytherapy for cervical cancer

Abstract: The use of brachytherapy in the treatment of cervical cancer has increased worldwide since its initial introduction over 100 years ago. However, certain aspects of the use of high-dose-rate (HDR) versus low-dose-rate (LDR) brachytherapy continue to be controversial, particularly the role of HDR in FIGO Stage III cervical cancer and the use of HDR with concurrent chemotherapy. This study represents a systematic literature review of prospective and retrospective series of patients with cervical carcinoma treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 59 publications
2
37
0
Order By: Relevance
“…7 While the quality of evidence from these trials was judged to be low to moderate, observational data in general has also reported equivalent survival outcomes for the two types of intracavitary systems. 2,4,7,9,11,2024 Our population-based data is in accord with these findings; overall, we noted similar survival outcomes for women treated with LDR and HDR brachytherapy.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…7 While the quality of evidence from these trials was judged to be low to moderate, observational data in general has also reported equivalent survival outcomes for the two types of intracavitary systems. 2,4,7,9,11,2024 Our population-based data is in accord with these findings; overall, we noted similar survival outcomes for women treated with LDR and HDR brachytherapy.…”
Section: Discussionsupporting
confidence: 87%
“…Brachytherapy allows dose escalation to the cervix and surrounding tissues and is critical in improving local control and decreasing the risk of pelvic relapse. 1,2 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also reported less late rectal complications in the group treated with HDR, thus it was hypothesized that these results could be due to low HDR brachytherapy doses delivered at point A [26]. A recent literature review concluded that HDR brachytherapy is an acceptable alternative to LDR brachytherapy in certain patients [27]. Overall, the review concluded that there was statistically equivalent local control, overall survival, and complication rates between HDR and LDR, and also found similar toxicity rates between HDR and LDR.…”
Section: The Role Of Radiation Therapy In Laccamentioning
confidence: 89%
“…2 Owing to the increased risk of complications in nearby critical structures, the amount of irradiation that can be delivered is limited and dose escalation is likely not the total solution to radiation resistance. 3 These facts underscore an urgent need for the development of more effective and less toxic novel therapeutic approaches. Therefore, investigators have turned to strategies for sensitizing CCs to radiation, and gene therapy represents one such modality.…”
Section: Introductionmentioning
confidence: 99%